Association between weight-adjusted waist index and severe periodontitis using NHANES 2009–2014 - Guiying He; Jiatong Zhang; Xinyue Liu; Zhengjie Qiu; Mengqing Yan; Mingxuan Zhang; Dongyang Wu; Lipei Liu; Cheng Ding; Xing Chen (Scientific Reports)
Abstract The Weight-adjusted Waist Index (WWI) is a novel anthropometric indicator for assessing obesity. Given the well-established association between obesity and periodontitis, this cross-sectional clinical study aimed to investigate the relationship between WWI and severe periodontitis while evaluating its potential as a simple predictive marker for periodontitis. The study analyzed periodontal examination data and WWI measurements from participants in the 2009–2014 National Health and Nutrition Examination Survey (NHANES), employing weighted logistic regression, smoothed curve fitting, and subgroup analyses. Among the 10,307 eligible participants, results demonstrated a significant positive correlation between WWI and the prevalence of stage III/IV periodontitis. After comprehensive adjustment for all confounding factors, each 1-unit increase in WWI was associated with a 1.19-fold higher risk of stage III/IV periodontitis (OR = 1.19, 95% CI 1.06–1.32, P = 0.007977). Subgroup analysis revealed that this association showed statistically significant variation only in the hypertension subgroup, indicating that the WWI-severe periodontitis relationship is particularly applicable to non-hypertensive individuals. These findings confirm that WWI can serve as a novel obesity-based predictive indicator for severe periodontitis.